DNA damage and lipid peroxidation vs. protection responses in the gill of Dicentrarchus labrax L. from a contaminated coastal lagoon (Ria de Aveiro, Portugal) - Ahmad, I. (2020)
The present research work aimed to investigate the damage vs. protection responses in gill of European sea bass (Dicentrarchus labrax) captured at a polluted coastal lagoon, Ria de Aveiro (Portugal), as a tool to evaluate the human impacts on environmental health. Damage was assessed as DNA strand breakage and lipid peroxidation (LPO) whereas protection was evaluated by measuring catalase (CAT), glutathione peroxidase (GPX), glutathione reductase (GR), glutathione S-transferase (GST), total glutathione (GSHt), thiols and metallothioneins (MT). Fish were caught at five locations: Gafanha (GAF), Rio Novo do Príncipe (RIO), Laranjo (LAR) and Vagos (VAG) presenting each a different recognized source of contamination, and Torreira (TOR), assumed as reference site. Among the surveyed sites, gill damage was observed only at GAF, as measured by DNA integrity loss and LPO increase. An overall induction in enzymatic antioxidant protection was perceptible in fish from GAF and VAG, expressed as higher GPX, GR and GST activities. In addition, LAR fish showed elevated GST and CAT activities. Thiols content was higher in all study sites irrespective to the pollution spectrum, whereas GSHt increase was only observed at GAF and VAG. The highest MT level was detected in fish from VAG and the lowest level from RIO suggesting a low contamination degree on this particular site. Globally, the results expressed site-specific response patterns, signalling two critical areas - GAF and VAG. Additionally, a joint analysis (damage vs. protection) allowed the following ordering of surveyed sites according to the contamination degree and risk to fish health; GAF>VAG>LAR>RIO>TOR. D. labrax gill responses demonstrated their efficacy as early warning signals of the contaminants presence. Moreover, the adopted approach, considering simultaneously protection responses and damaging effects, also revealed its usefulness on the pollution extent assessment.